Implementasi Metode Dempster-Shafer untuk Mendeteksi Penyakit Diabetes Mellitus - Januar Dwi Amanda; Nurul Hidayat; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Early detection can minimize the risk of death from Diabetes Mellitus disease and first treatment for this disease. The detection that existed so far is still don manually, which means it depend on the expert who very limited on itquantity and also it diagnosis are costly. The disease expert can detect Diabetes Mellitus earlier and cheap. On this research this kind of Diabetes Mellitus that can be detected as many as 3 disease using Demspster-Shafer Method with input from user of symptoms. The method is used to analyze the data of system accuracy test between the detection and the result of Dempster-Shafer method calculation with 11 case data has the data accuracy level of 81,81%